PERAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR: KAJIAN STUDI LITERATUR - Riska; Sinar Kumalasari; Cici Diah Anggelia; Mariano Satya Pramularsih; Selvi Tando; Eka Yuliani Zandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of Information and Communication Technology (ICT) continues to shape primary education in many parts of the world. In practice, however, schools do not experience these changes in the same way. In Indonesia, for instance, teachers often struggle with very basic issues such as unstable internet access, limited devices availabilities, and uneven digital skills among both teachers and students. Meanwhile, countries like Germany, Finland, and Ireland deal with a different set of concerns. Their discussions tend to focus on how confident teachers feel when using technology, how well students develop computational thinking skills, and whether online training programs actually help teachers in their everyday classroom work. These differences made our reseachers team-mates curious about what current research really says about the role of ICT in improving learning at the primary level. This study, therefore, brings together findings from 13 journal articles published between 2021 and 2025, covering several countries including Indonesia, Taiwan, Germany, Finland, China, and Ireland. Using a thematic meta-synthesis approach, the articles were reviewed through four steps: selecting the studies, extracting key points, grouping similar ideas, and interpreting the overall themes that emerged.The review is expected to offer a clearer and more grounded picture of how ICT is being used, what benefits it brings, and what barriers still remain in different educational settings. Hopefully, these insights can help teachers, schools, and policymakers think more realistically about how technology can support primary education.